Construction of a hybrid graphene oxide/nanofibrillated cellulose aerogel used for the efficient removal of methylene blue and tetracycline. (March 2021) - Wang, Zhongguo; Song, Lian; Wang, Yaquan; Zhang, Xiong-Fei; Yao, Jianfeng
Abstract: A composite graphene oxide (GO)/nanocellulose aerogel was prepared by dispersing cellulose nanofibrils (CNFs) into GO nanosheets. CNFs with high aspect ratios and negative potential helped the exfoliation of GO flakes without the need of a chemical linker via steric hindrance and electrostatic repulsion. Water purification tests were performed using methylene blue (MB) and tetracycline (TC) as model pollutants. The composite aerogel obeyed a pseudo-second-order model and Langmuir adsorption isotherm. The composite aerogel possesses a maximum adsorption capacity of 111.2 mg/g for MB and 47.3 mg/g for TC. Meanwhile, the aerogel can be easily recycled and regenerated using ethanol. After three cycles, the aerogel can maintain a high removal efficiency for MB (98%) and TC (97%). The adsorption mechanism was mainly ascribed to electrostatic attraction and π-π interactions. Highlights: Cellulose fibers promote the dispersion and exfoliation of GO flakes. A composite GO/nanocellulose aerogel has been fabricated. The aerogels exhibit high adsorption for methylene blue and tetracycline. The adsorption mechanism is due to electrostatic attraction and π-π interactions. The aerogels have good reusability and recyclability.